Cooperative indexing in U.P Diliman Library system with implications to the Index to Philippine Periodicals (IPP) a basis for an action plan - Manaay, Lyle D.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
The study sought to find out what seems to be the prevailing problem of cooperation among the U.P. Diliman Library system and what measures can be adopted to alleviate problems posed by librarians tasked with indexing Philippine Periodicals. Twenty-three out of 27 librarians from 24 libraries of the U.P. Diliman Library system responded to the survey.
Results reveal that out of the 24 libraries involved, only 9 are in cooperative indexing or contributing to the production of the Index to Philippine Periodicals (IPP).On the IPP evaluation, a 5-point scale was used with 3 as average. IPP received 4.12, 4.11 and 4.05 point rating scores each on comprehensiveness, appropriateness of subject headings for the user, clearness of types, respectively. Ratings on arrangement are 3.88; currency, 3.83; consistency of entries, 3.82 and quality of paper, 3.67. Overall, IPP got a good score. On the attitude and behavior of the participating librarians in the cooperative indexing, findings show the following problems: indexing is not a collective effort; lack of staff to index; no time to index; lack of communication with other libraries and with the Bibliography and Indexing Section (BIS); and limited Filipiniana periodicals to index. Some librarians do not follow the regular schedules of submission of index entries to the BIS. They do not attend consultative meetings.
The study recommends that all libraries within the U.P. Diliman Library System be required to submit index entries to the BIS. To foster cooperation among members regular meetings should be held. Lastly, a technical group or a Cooperative Indexing Team should be created composed of senior librarians, which will not only be a policy making body as far as IPP is concerned but will, as well, monitor the activities and concerns of IPP.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman